Why institutions matter in the Eurozone: reforming EU economic governance - Thillaye, Renaud; Kouba, Ludek; Sachs, Andreas (London, 2014)
"The debate about the Eurozone’s future usually centres on a clash between economics and politics. Giving the EU greater oversight powers and more spending capacity is said to be the only viable long run solution, but there is little popular appetite for this option. As a result, the Eurozone seems destined to ‘muddle through’ to the benefit of creditor countries. This paper seeks to offer fresh insights into this debate by highlighting a third, overlooked dimension, namely the challenge of making governance work in practice. Recommendations for new Eurozone institutions come at a time when EU mechanisms and funds are under fire for being too complex and ineffective. They are said to create moral hazard, lack flexibility, and to heighten bureaucratic red tape. The EU, and the Eurozone, may be facing a crisis of maturity whereby the creation of new institutions risks making matters worse. To illustrate this argument, the paper assesses the desirability and feasibility of two possible governance innovations among those currently under discussion in the Eurozone: a mechanism of wage coordination, and contractual arrangements (or ‘reform contracts’) between the EU and member states. Beyond economic and political arguments, the paper invites commentators and policymakers to shift their focus of attention from conception to implementation."